Development of Creative Advertising. Past and Present - Vázquez Gestal, Montse (2011)
In this article we try to perform a brief tour around the history of creativity up to the present. This research analyzes this concept from its very beginning focusing on its application to the advertising field, where the cited concept gets reinvented again and again in order to explore its new possibilities and situations.